Experimental comparison between R152a and R134a working in a refrigeration facility equipped with a hermetic compressor. (December 2015) - Cabello, R.; Sánchez, D.; Llopis, R.; Arauzo, I.; Torrella, E.
Highlights: An experimental comparison between R134a and R152a is presented and commented. A reduction of about 10% in cooling capacity was registered by using R152a. A reduction up to 16% in electrical power consumption was registered by using R152a. An improvement up to 13% in COP was obtained using R152a. Aside safety issues R152a was used successfully as a "drop-in" refrigerant for R134a. Abstract: The EU Regulation 517/2014 has recently been approved in a further attempt to curb the effects of Global Warming. As a consequence, the refrigeration sector is moving towards refrigerants with a low Global Warming Potential (GWP100 ) in accordance with the limit fixed by these regulations (150). In this regard, the old refrigerant R152a attracts renewed interest due to its low GWP (138) and its similarity to R134a. The present work shows the results of using R152a in a vapour compression plant equipped with a hermetic compressor and an IHX designed for R134a. The refrigerant was replaced by a conventional "drop-in" process in order to carry out an energy comparison. The results have revealed an improvement in the COP with R152a up to 13% despite a reduction in the cooling capacity of about 10%. During the test campaign, R134a hermetic compressors have been shown to be capable of operating with R152a.